BIOACTIVE COMPOUNDS IN DIASPORES OF Astronium urundeuva (M.Allemão) Engl. FOR QUALITY MAINTENANCE DURING STORAGE - Senigalia, Ritielly Laiany Carvalho; Coelho, Maria de Fátima Barbosa; Kratz, Dagma; Camili, Elisangela Clarete; Souza, Edila Cristina de; Felix, Francival Cardoso (Floresta, 2023)
The success of seed production and marketing depends on ideal conditions for storage. Some forest species have seed conservation problems due to the high incidence of fungi that reduce physiological quality. Thus, the objective was to evaluate the effectiveness of the application of bioactive compounds in diaspores of Astronium urundeuva (M.Allemão) Engl. (Anacardiaceae) to maintain physiological quality and reduce the incidence of fungi during storage. For this, two factorial trials were set up: (i) application of four essential oils (cinnamon, clove, orange and melaleuca) at five concentrations (0.00, 1.25, 2.50, 3.75 and 5.0 mL.kg-1); and (ii) five plant extracts (clove, cinnamon, quina, garlic and lemongrass) at five concentrations (0%, 25%, 50%, 75% and 100%). Diaspores were evaluated at 0, 30, 60, 90, 120, 150 and 180 days for germination, seed vigor and fungal incidence. The essential oils of clove (4.6 mL.kg-1) and melaleuca (3.7 mL.kg-1) and plant extracts of clove (71%) and lemongrass (73%) can be applied to maintain physiological quality and reduce the incidence of fungi during the storage of A. urundeuva diaspores. In addition to these, the essential oils of cinnamon (3.8 mL.kg-1) and orange (4.0 mL.kg-1) and plant extracts of cinnamon (72%) and quina (74%) can be used as an alternative to synthetic fungicide. Therefore, the application of products based on natural bioactive compounds is an alternative to the use of chemicals in sanitary control during the storage of A. urundeuva seeds.